The Development of Wizer.Me-Based Student Worksheets to Improve Students’ Mathematical Creative Thinking Ability - Sugiarti, Sri; Luritawaty, Irena Puji; Sumartini, Tina Sri (Universitas Wiralodra, 2026)
This study aimed to develop Wizer.Me-based Student Worksheets (LKS) on trigonometric functions to enhance senior high school students’ mathematical creative thinking skills. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The developed product was validated by a subject-matter expert and a media expert, and subsequently tested for its practicality and effectiveness. The trial subjects consisted of two mathematics teachers and nine twelfth-grade students. The validation results indicated that the worksheets were categorized as highly valid, with a percentage of 89.5% from the subject-matter expert and 85% from the media expert. The practicality test showed that the worksheets were considered highly practical, with an average percentage of 88.5%. The effectiveness test, based on students’ response questionnaires, indicated a highly effective category with a percentage of 87.33%. In addition, the results of the mathematical creative thinking skills test demonstrated improvement, with the N-gain scores falling within the moderate to high categories, particularly on the indicators of fluency and elaboration. Based on these findings, it can be concluded that the developed Wizer.Me-based Student Worksheets are valid, practical, and effective in improving students’ mathematical creative thinking skills. Therefore, the Wizer.Me-based worksheets are feasible to be used as an alternative instructional medium in mathematics learning, particularly on trigonometric function topics at the senior high school level.Bottom of Form